STRATEGI KEPEMIMPINAN KEPALA MADRASAH DALAM MENINGKATKAN MUTU LAYANAN PENDIDIKAN DI MI MAMBA’UL HUDA AL-ISLAMIYYAH PONOROGO - Marwa Tri Handayani; Lilik Huriyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The role of leadership in education is essential. Madrasah principals are not limited to carrying out administrative functions but also play a role in establishing direction, vision, and targeted goals to achieve improvements in the quality of education. This study aims to study and analyze various leadership strategies used by principals to improve the quality of educational services. This study uses a qualitative method with a case study approach to explore in-depth the leadership strategies of madrasah principals in improving the quality of educational services at MI Mamba'ul Huda Al-Islamiyyah Ponorogo. One of the madrasah principals' strategies in improving the performance of madrasahs is through providing guidance to teachers. This guidance is carried out so that teachers carry out their duties honestly, responsibly, effectively, and efficiently. MI Mamba'ul Huda Al-Islamiyyah is able to build an educational environment that is religious, collaborative, and oriented towards the development of students' overall potential.